2006
DOI: 10.1002/pds.1298
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists' attitudes towards the reporting of suspected adverse drug reactions in Norway

Abstract: The pharmacists had positive attitudes towards pharmacovigilance, but very little experience with reporting. The educational programme clarified their role and increased their knowledge about the reporting requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
85
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 22 publications
25
85
1
2
Order By: Relevance
“…[25][26] Well designed educational training programs and workshops on pharmacovigilance may clarify and enhance the knowledge of both students and healthcare professionals about the requirements of ADR reporting. 25,28,30 There were also some misconceptions on the type of ADRs that are required to be reported. The majority of students mistakenly believed that establishing association between ADR and the suspected drug is compulsory before reporting it.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26] Well designed educational training programs and workshops on pharmacovigilance may clarify and enhance the knowledge of both students and healthcare professionals about the requirements of ADR reporting. 25,28,30 There were also some misconceptions on the type of ADRs that are required to be reported. The majority of students mistakenly believed that establishing association between ADR and the suspected drug is compulsory before reporting it.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to that of previous reports involving healthcare professionals. 11,38 Whether the students had taken a course related to pharmacovigilance was significantly associated with the belief that the pharmacovigilance topic was not well covered in the schools' curricula. More than half of the students indicated that they had attended pharmacovigilance courses previously, reflecting a possible lack of uniformity and comprehensiveness in the curricula related to the teaching of pharmacovigilance in the faculties of pharmacy throughout Malaysia.…”
Section: Discussionmentioning
confidence: 99%
“…Educational training programs, however, can clarify and enhance the knowledge of healthcare professionals regarding ADR reporting requirements. [38][39][40] About 18% of the pharmacy students correctly answered the survey question related to uncertainty about the causal relationship between the suspected ADR and the drug being a barrier to ADR reporting. This finding is consistent with those of similar reports about healthcare professionals elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Granas et al (11) Educational intervention study assessing the effect of an educational program on pharmacovigilance for pharmacists in Norway. They observed that lack of trust, time and knowledge about how to report an adverse reaction could prevent them from reporting.…”
Section: Author Rationalementioning
confidence: 99%